Periodized strength training: A critical review - Fleck, S. J. (The Journal of Strength and Conditioning Research, 1999)
Variation or periodization of training is an important concept in designing weight-training programs. To date, the majority of studies examining periodization of weight training have used a traditional strength/power training model of decreasing training volume and increasing training intensity as the program progresses. The majority of these studies have used males as subjects and do support the contention that periodized programs can result in greater changes in strength, motor performance, total body weight, lean body mass, and percent body fat than nonperiodized programs. However, studies are needed examining why periodized training is more beneficial than nonperiodized training. Studies are also needed examining the response of females, children, and seniors to periodized weight-training programs and the response to periodized models other than the traditional strength/power training model.